2000
DOI: 10.1123/pes.12.4.413
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effects of an 8-Week Diet, Exercise, and Educational Camp Program on Obese Children

Abstract: One hundred and ninety-four children enrolled in a summer weight loss camp program (64 boys and 130 girls, aged 12.6 ± 2.5 years) and were assessed for body mass and stature on arrival. One hundred and fourteen subjects were assessed for waist circumference, with a subgroup of 14 boys assessed on 8 skinfold thicknesses, 9 circumference measures, and a self-paced walk test to evaluate aerobic performance. A further group of 40 girls were assessed on 3 psychometric variables (self concept, body esteem, and body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 0 publications
1
28
0
1
Order By: Relevance
“…However, a majority of the programs described extend for periods of up to 10 months, involving continuous and intensive treatment and requiring incentives to ensure that participants adhere, which cannot be applied in daily practice. 62,66 The results of these programs are not so encouraging, although when applied to children the results are better. 62,67 A majority of dietary intervention techniques focus on reducing the consumption of fats, even when dietary fat may not be a significant cause of obesity.…”
Section: Complications Of Childhood Obesitymentioning
confidence: 97%
“…However, a majority of the programs described extend for periods of up to 10 months, involving continuous and intensive treatment and requiring incentives to ensure that participants adhere, which cannot be applied in daily practice. 62,66 The results of these programs are not so encouraging, although when applied to children the results are better. 62,67 A majority of dietary intervention techniques focus on reducing the consumption of fats, even when dietary fat may not be a significant cause of obesity.…”
Section: Complications Of Childhood Obesitymentioning
confidence: 97%
“…16 Programs that have been described are developed with continuous and intense treatment, requiring some type of incentive for individuals to take part weekly or even several times a week, which curtails their applicability on practice. 17,18 In the scope of aspects highlighted by Barlow & Dietz,19 obesity treatment should aim at changes in behavior. They recommend that programs should achieve permanent changes and not rely on short-term dieting or exercise programs aimed at rapid weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Preliminary evidence has also suggested that participation in weight loss camps that involve physical activity can affect mental health outcomes positively in obese children. [12][13][14] One study reported that obese adolescent girls who participated in an aerobic exercise intervention had lower depression scores than did girls allocated to other types of exercise or usual care. 15 However, all studies contained small samples and did not use randomized, controlled trial (RCT) methods.…”
mentioning
confidence: 97%